Angioprevention of Urologic Cancers by Plant-Derived Foods. - García-Caballero, Melissa; Torres-Vargas, José Antonio; Marrero Capitán, Ana Dácil; Martínez-Póveda, Beatriz Amparo; Medina-Torres, Miguel Ángel; Rodríguez-Quesada, Ana María (MDPI, 2022)
The number of cancer cases worldwide keeps growing unstoppably, despite the undeniable advances achieved by basic research and clinical practice. Urologic tumors, including some as prevalent as prostate, bladder or kidney tumors, are no exceptions to this rule. Moreover, the fact that many of these tumors are detected in early stages lengthens the duration of their treatment, with a significant increase in health care costs. In this scenario, prevention offers the most cost-effective long-term strategy for the global control of these diseases. Although specialized diets are not the only way to decrease the chances to develop cancer, epidemiological evidence support the role of certain plant-derived foods in the prevention of urologic cancer. In many cases, these plants are rich in antiangiogenic phytochemicals, which could be responsible for their protective or angiopreventive properties. Angiogenesis inhibition may contribute to slow down the progression of the tumor at very different stages and, for this reason, angiopreventive strategies could be implemented at different levels of chemoprevention, depending on the targeted population. In this review, epidemiological evidence supporting the role of certain plant-derived foods in urologic cancer prevention are presented, with particular emphasis on their content in bioactive phytochemicals that could be used in the angioprevention of cancer.
Keywords: Aparato urinario - Cáncer - Prevención; Sustancias fitoquímicas; Angiogenesis; Chemoprevention; Angioprevention; Phytochemicals; Urologic cancer; Prostate cancer; Bladder cancer; Kidney cancer